ANALISIS PENDAPATAN PETERNAK AYAM RAS PETELUR DI ASOSIASI BERKAH TELUR MAKMUR PURWOREJO - Musholihah, Amam; Zulfanita, Zulfanita; Mudawaroch, Roisu Eny (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2022)
This study aims to determine: 1) production costs, revenues, income and profits of laying hens at the Berkah Telur Makmur Association in one production period and 2) factors influence the profit of laying hens at the Berkah Telur Makmur Association in one production period. This study used a descriptive method with the research location at the Berkah Telur Makmur Association of Purworejo. The sample in this study were 50 farmers. Sampling was done by using saturated sampling method. Data analysis uses production costs, revenues, incomes, profits and profit factors. The results of data analysis showed that the laying hens business in the Berkah Telur Makmur Association was profitable. Factor that has a significant effect of laying hens is the price of electricity and water. Keywords: Laying, Income, Profit Factor